ETHICS IN MARKETING - BRANDS MUST WORK WITH TRANSPARENCY AND CONSUMER TRUST - Mamatkulova Shoira Djalolovna (Web of Journals Publishing, 2025)
In this article, we consider ethical issues in marketing, with an emphasis on the need for brands to work with transparency and consumer trust. Special attention is paid to the practices of honest and open communication with the target audience, compliance with standards of social responsibility and consumer protection. In the face of increasing competition and increased consumer expectations, brands must not only offer high-quality products and services, but also maintain trusting relationships with customers.
Keywords: Ethics in marketing, brand transparency, consumer trust, social responsibility, marketing strategy, honesty in advertising, brands and customers, corporate responsibility, sustainable development, brand reputation.